Genomic variation in the MAP3K5 gene is associated with β-thalassemia disease severity and hydroxyurea treatment efficacy. (April 2013) - Tafrali, Christina; Paizi, Arsinoi; Borg, Joseph; Radmilovic, Milena; Bartsakoulia, Marina; Giannopoulou, Emily; Giannakopoulou, Olga; Stojiljkovic-Petrovic, Maja; Zukic, Branka; Poulas, Konstantinos; Stavrou, Eleana F; Lambropoulou, Polyxeni; et al.
Aim: In this study we explored the association between genetic variations in MAP3K5 and PDE7B genes, residing on chromosome 6q23, and disease severity in β-hemoglobinopathy patients, as well as the association between these variants with response to hydroxyurea (HU) treatment. Furthermore, we examined MAP3K5 expression in the context of high fetal hemoglobin (HbF) and upon HU treatment in erythroid progenitor cells from healthy and KLF1 haploinsufficient individuals.Materials & methods: For this purpose, we genotyped β-thalassemia intermedia and major patients and healthy controls, as well as a cohort of compound heterozygous sickle cell disease/β-thalassemia patients receiving HU as HbF augmentation treatment. Furthermore, we examined MAP3K5 expression in the context of high HbF and upon HU treatment in erythroid progenitor cells from healthy and KLF1 haploinsufficient individuals.Results: A short tandem repeat in the MAP3K5 promoter and two intronic MAP3K5 gene variants, as well as a PDE7B variant, are associated with low HbF levels and a severe disease phenotype. Moreover, MAP3K5 mRNA expression levels are altered in the context of high HbF and are affected by the presence of HU. Lastly, the abovementioned MAP3K5 variants are associated with HU treatment efficacy.Conclusion: Our data suggest that these MAP3K5 variants are indicative of β-thalassemia disease severity and response to HU treatment. Original submitted 24 September 2012; Revision submitted 4 February 2013